Management of village funds based on Islamic Shari'ah: A literature study - Rina Sulistyowati; Mas’ádah; Irma Indira; Mesra Berlyn Hakim (Institute of Computer Science (IOCS), 2023)
Village fund financial management is regulated in Permendagri No. 20 of 2018, which states that village financial management is an activity that includes planning, implementation, administration, reporting and accountability of village finances, and must be based on transparent, accountable, participative, orderly and budgetary principles. This research method uses library research, in which the data or materials used in completing the research come from the library, either in the form of books, encyclopedias, dictionaries, journals, documents, magazines and others. The results explain that the financial management of village funds based on Islamic shari'ah teaches to always instill the nature of openness/transparency, truth, fairness, honesty (accountable), trust and accountability in carrying out a plan, implementation, management and reporting of accountability in life both in the form of individuals and society, and must be accountable to God.Research on the financial management of village funds based on Islamic sharia is important because it is expected to reduce the level of village fund corruption and fraud that exists in village government.